Organised crime in inter-war Britain and its impact on society - Řídký, Daniel (Univerzita Pardubice, 2023)
This bachelor thesis focuses on the inter-war period in Britain. The theoretical part´s main aim is to show the reader what the life in inter-war Britain´s society was like. It deals with the worldwide economic crisis and how it affected the people, consequences of war and most importantly the rise of organised crime gangs which is the main concern of the second chapter. The analytical part tries to point out the similarities and differences between the popular novel Brighton Rock and the real events. It comments on the historical associations, gang culture and on the stereotypes based on the character descriptions and actions in the novel.
Organizovaný zločin v meziválečné Británii a dopad na společnost
Keywords: organizovaný zločin; gangy; Brighton; Sabini; závodiště; meziválečná Británie; Greene, Graham; organised crime; gangs; Brighton; Sabini; racecourse; inter-war Britain; Greene, Graham